KETERAMPILAN MENULIS LAPORAN PENGAMATAN SISWA KELAS V SD MELALUI MODEL EXAMPLES NON EXAMPLES - Dewi, Titi Purnama; Rahayu, Galih Dani Septiyan (IKIP Siliwangi, 2021)
This study is entitled to improve the skills of writing observational reports of fifth-grade elementary school students through the Examples Non-Examples Model, this title is motivated by consideration of the lack of student skills when writing reports based on learning objectives, material criteria, and characteristics of fifth-grade elementary school students. The purpose of this research is to find out the improvement in the skills of fifth-grade elementary school students in writing observation reports through the Examples Non-Examples Model in elementary schools. The study conducted a qualitative approach by observing and evaluating in the form of non-test techniques using questionnaires and observation sheets. This research will focus on